Konsep Kebebasan Jean-Paul Sartre dan Ajaran Gereja Katolik Dalam Ensiklik Evangelium Vitae terkait Tindakan Aborsi - Lorinanto, Exel; Papoto, Dandi; Kisa, Ignasius; Tohea, Krisjumon (Jurnal Seri Mitra (Refleksi Ilmiah Pastoral), 2025)
This paper explores the comparison between the concept of freedom in the existentialist philosophy of Jean-Paul Sartre and the moral teachings of the Catholic Church as articulated in the encyclical Evangelium Vitae, particularly in the context of abortion decisions. Sartre views freedom as an essential and absolute characteristic of human beings, wherein each individual is fully responsible for their life choices without reference to external norms. Within this framework, the decision to undergo an abortion can be seen as an authentic expression of individual freedom. In contrast, the Catholic Church teaches that human freedom must be directed toward truth and the objective value of life, which comes from God. Abortion, in the Church’s view, constitutes a violation of the irreplaceable dignity of human life. Using a qualitative approach with textual analysis of Sartre’s works and Church documents, especially Evangelium Vitae, this paper reveals the tension between individual autonomy and the demands of objective moral truth. The study underscores the importance of a balanced philosophical and theological reflection in understanding human freedom, particularly in complex ethical issues such as abortion.